Factors Influencing Seasonal and Daily Dynamics of the Genus Stomoxys Geoffroy, 1762 (Diptera: Muscidae), in the Adamawa Plateau, Cameroon - Sevidzem S. Lendzele; Mavoungou J. François; Zinga-Koumba C. Roland; Koumba A. Armel; Gérard Duvallet (International Journal of Zoology)
The rangelands of the Vina Division on the Adamawa Plateau are densely infested with Stomoxyinae, but little is known about their species composition and ecology. A trap-transect survey was carried out in three villages: Galim, Mbidjoro, and Velambai, using Nzi (n = 3), Vavoua (n = 3), and Biconical (n = 3) traps, all baited with octenol. Three traps of each trap type were set in each of the study villages, and collections were carried out daily. In total, 3,762 Stomoxys spp. were collected from October 2016 to June 2017 and identified using standard keys into five species: Stomoxys niger niger, S. calcitrans, S. niger bilineatus, S. omega, and S. xanthomelas. Galim recorded the highest apparent density of stomoxyines (30 stomoxyines/trap/day) with a statistically significant difference (p<0.05). The Vavoua trap was an ideal tool for Stomoxyinae collection. Stomoxyines abundantly occurred at the end of the dry season (March 2017) and beginning of the rainy season (May 2017). The monthly rainfall positively influenced monthly ADTs of Stomoxyinae. Their diurnal biting activity was bimodal in the rainy season and unimodal in the dry season. The daily activity peak was between 14 h and 16 h with a mean temperature of 31°C, a mean wind speed of 1.5 m/s, and a mean humidity of 50%. The daily trap catch was positively influenced by temperature and wind speed but negatively influenced by rainfall and air humidity. Weather variables influenced Stomoxys spp. monthly and daily ADTs.